At the frontier of particle physics - edited by M. Shifman (World Scentific, 2001)
Part 6: Quark-Hadron Duality, QCD Sum Rules, a modern perspective, topics in the Heavy Quark Expansion, Weak decays of heavy quark, Renormalons and power correction, Part 7: Confinement , magnetic Zn Symmetry and Low-Energy Effective Theory of Gluodynamics...